Household storage, surplus and supra-household storage in prehistoric and protohistoric societies of the Western Mediterranean. - Georgina Prats; Ferran Antolín; Natàlia Alonso (PLoS ONE, 2020)
The objective of this paper is to assess foodstuff storage throughout Recent Prehistory (5600-50 BCE) from the standpoint of the three different types (household, surplus and supra-household) identified in the northeast of the Iberian Peninsula. The volumetric data of the underground silos serves as a proxy to evaluate the link between them and the agricultural systems and technological changes. The study also assesses the ability, and specifically, the will of the ancient communities of the northeastern Iberia to generate domestic and extra-domestic surpluses.